Superior capacitive performance of nitrogen-doping three-dimensional hydrangea-like porous carbons derived from oxidized coal tar pitch polymerized p-phenylenediamine. (15th August 2022) - Zhuang, Qi-Qi; Cao, Jing-Pei; Yang, Zhi-Hui; Wei, Yu-Lei; Wu, Yan; Zhao, Xiao-Yan; Sun, Jin-Hui; Wei, Yan-Bin
Graphical abstract: Highlights: Coal tar pitch was oxidized by KMnO4 . Nitrogen precursors were synthesized by chemical oxidative polymerization. Nitrogen-doping three-dimensional hydrangea-like porous carbons was prepared. High energy density (56.4 Wh kg −1 ) in EMIMBF4 electrolyte. Abstract: Nitrogen-doping three-dimensional hydrangea-like porous carbons (NHPCs) were prepared by coal tar pitch oxidized by KMnO4 (OCTP) as carbon precursor and p-phenylenediamine (pPDA) as nitrogen source. The terminal amine group on the pPDA and the oxygen-containing functional group on the OCTP were grafted together by chemical oxidative polymerization. Not only successfully achieved nitrogen-doping, but also the benzene ring in pPDA could occupy the branching space of polycyclic aromatic hydrocarbons in OCTP and reduce its irreversible accumulation. The as-prepared NHPCs showed a unique three-dimensional hydrangea-like structure, which could provide large specific surface area (2237 m 2 g −1 ), abundant micro/mesopores and high nitrogen content (3.7%). Remarkably, NHPC-600 exhibited excellent electrochemical performance as the electrode material of supercapacitors, such as a high specific capacitance up to 423 F g −1 at 0.1 A g −1 and long cycle stability (maintaining 94.3% of the initial capacitance after 10, 000 cycles) in 6 M KOH. Simultaneously, NHPC-600 achieved a higher working voltage (3.6 V) in EMIMBF4 electrolyte, thereby obtaining a high energy density (56.4 Wh kg −1 ).